Blair’s Social Reforms and the Third Way - Mokeddem ,Ahmed Rafik; Bouhali, Mohamed; Sedekki ,Mohamed (Faculty of Letters and Foreign Languages Department of English, 2019)
This thesis highlights the New Labour’s social policy between1997-2007. After its remarkable victory in the 1997 general elections, the New Labour under the leadership of Tony Blair has seen the modernisation of the welfare state to be its major task .Blair launched a set of social reforms that would improve ordinary people’s life. To achieve his goal he adopted the Third Way, a concept which tries reconcile the New Right and the Old Left principles .What motivated us to do this research is to find out what pushed the Labour Party break away with its old policy, what made Blair’s reforms revolutionary and most importantly what impact these reforms had on the British Society. Some reports consider that Blair succeeded in improving people’s living conditions; however other think that this success was temporary and many issues needed to be dressed